Adaptação transcultural e análise das propriedades de medida da versão brasileira do COPD Exacerbation Trigger Inventory (CETI) - Tacao, Guilherme Yassuyuki [UNESP] (2023)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is currently the third leading cause of death in the world, with the highest incidence in low- and middle-income countries. In Brazil, a prevalence of 19% can be observed among adults and the elderly. Smoking is the main risk factor, however, occupational and environmental exposures are important for the onset and progression of the disease in developing countries. Objectives: The objective of this study was to verify if the construct of the Portuguese version of the COPD Exacerbation Trigger Inventory (CETI) is valid and reproducible for exacerbations in individuals with COPD. Material and methods: For the present study, individuals with COPD in the city of Presidente Prudente/SP were evaluated, regardless of gender. The study was carried out in three parts, the first part being the translation of the questionnaire into Portuguese, the second part application of the questionnaire in Portuguese, in addition to the Clinical Control of COPD Questionnaire (CCQ), dyspnea assessment (MRC) and Assessment Test. of COPD (CAT) together with the pulmonary function test (spirometry), later, the third part, they returned one week later for reapplication of the CETI scale. Results: A total of 58 individuals were evaluated; however, 8 were excluded due to normal spirometry results (n=2), failure to attend both complete assessments (n=4), and failure to respond to telephone contact (n=2). In the disease stage classification, we observed a higher number in GOLD II and a predominance of males. Regarding the values in CCI for intra-observer reproducibility between A0 and A1, moderate to high agreement was obtained for psychological triggers, air pollution/irritants, and physical activity. When comparing the applied days, there were differences in responses for psychological triggers (p=0.001), climatic triggers (p=0.016), and physical activity (p=0.015). Final considerations: Based on the presented results, it is possible to conclude that the Portuguese version of the questionnaire demonstrated good agreement and moderate to excellent reproducibility with the evaluated COPD sample. However, it should be noted that there was no agreement among all the analyzed triggers when comparing the applied days.